WHEEL TRACK DEFORMATIONS IN ASPHALT CONCRETE PAVEMENTS - Yuldashev, Akmal Temirovich; Narmanov, Akbar Kuziboyevich (Educational Research in Universal Sciences, 2022)
The article describes the reasons for the appearance of wheelbase deformations that occur on roadways with asphalt concrete pavement, their types and methods of their elimination, which are theoretically hit and analyzed